PENYUSUNAN LAPORAN KEUANGAN BERBASIS SYSTEM MELALUI PEMANFAATAN SOFTWARE ACCURATE V5 BAGI SISWA SMK SATRIA DI WILAYAH SRENGSENG JAKARTA BARAT - Putri Dwi Wahyuni; Wieta Chairunesia; Rini Marlina (LPPM ITB AAS Indonesia Surakarta, 2022)
The increasingly rapid development of Technology and Communication (ICT) in the era of the industrial revolution 4.0 brought changes in all lines of activity. This development changed the social order which initially used the old (conventional) method into new, more technology-based methods. Information technology has changed the accounting process from traditional accounting to information technology accounting. One of the technological and communication developments that occur in the learning process is the preparation of financial reports that previously used manuals to become system-based, namely by using accounting software. Accurate V5 accounting software training can provide benefits for Satria Vocational School students in improving learning and competence in compiling financial reports for service, trading and manufacturing companies using Accurate V5 software. The aim of this training is for Satria Vocational High School students to understand and use Accurate V5 accounting software well. After this activity students are expected to be able to improve learning and competence in the field of accounting in compiling financial reports quickly and accurately using Accurate v5 accounting software so that they can compete with graduates from other schools in the world of work. Overall, the trainees understand the material presented and can use accounting software (Accurate v5) well in preparing financial reports. The activity went well and the participants were actively discussing Keywords: accurate v5 training, SMK Satria, Srengseng